Early predictors of reading success in first grade - Sucena, Ana; Garrido, Cristina; Marques, Cátia; Lousada, Marisa (Frontiers in Psychology, 2023)
Reading acquisition is a complex process that can be predicted by several components which, in turn, can be affected by the orthography depth. This study aims to explore the early predictors of (un)success in reading acquisition within an intermediate transparent orthography. At the beginning of the school year, 119 European Portuguese-speaking first graders were assessed regarding (i) sociodemographic variables: mothers' education and socioeconomic status (SES); (ii) cognitive variables: phonological working memory and vocabulary; (iii) reading-related variables: letter-sound knowledge, phonemic awareness, and rapid naming. Results of the three variable clusters were correlated with the final classification obtained in the Portuguese discipline. Specifically, there was a correlation between the Portuguese discipline classification with all reading and cognitive-related variables, with the highest correlations occurring with mother education and letter spelling. A regression analysis was conducted to assess the predictor impact of mother education and letter spelling (variables that correlated stronger with the Portuguese classification) on Portuguese classifications. Letter spelling was the sole significant predictor of the Portuguese classification. Based on these results, a path analysis was run to test whether letter spelling is a mediator of the relationship between the mother's education and the Portuguese classification. The results of the model test yielded a reasonable fit, indicating a relationship between the mother's education and letter spelling, which in turn, relates to the Portuguese classification. The identification of reading predictors in an intermediate-depth orthography such as European Portuguese contributes to more accurate identification of at-risk children.